Communicating Critics: An Analysis of Kiky Saputri’s Roasting towards “Crazy Rich Andara” - Lambok Hermanto Sihombing; Puji Lestari (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2022)
Comedy has been a part of Indonesian culture. The development of comedy that can be seen nowadays is Stand-up Comedy. One of the Stand-up Comedy techniques that has been favored by Indonesian people is roasting. It is a series of jokes that functions to criticize a certain person such as a politician, celebrity, or minister. This study aims to analyze Kiky Saputri’s roasting to the Crazy Rich Andara named Raffi Ahmad. The data was taken from one of the videos from Indosiar YouTube channel. This study has applied the theory of Humor and Satire particularly Horatian and Juvernalian satire proposed by Holman and Rhetorical approach to communication to find out the meaning of Kiky's roasting content. The findings have revealed that each roasting delivered by Kiky does not only contain entertaining materials, but also critics to Raffi Ahmad